VISUAL MERCHANDISE DAN ATMOSFER TOKO: PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN IMPULS - Pancaningrum, Erminati (Jurnal Ilmu Ekonomi dan Pembangunan, 2017)
This study aims to determine the influence of visual merchandising and store atmosphere against impulse buying on the visitors of  Matahari Department Store at City of Tomorrow, Surabaya. The method used is explanatory research; the data are collected through questionnaires and documentation. Those are analyzed using multiple linear regression statistical methods. The results of data analysis showed that the better visual merchandising and store atmosphere, the more it will increase impulse purchasing on consumers. Test hypothesis states that the visual merchandising and store atmosphere significantly influence consumers impulse buying in Matahari Department Store City of Tomorrow Surabaya. Visual merchandising is realized by a variety of stimuli, such as the arrangement of the product, the selection of beautiful colors for the outlets, lighting inside the store will make consumers comfortable shopping, which can result in unplanned purchases. Atmospheric stores increases the likelihood of impulsive behavior. Atmosphere fun and interesting stores can stimulate the purchase of the response of a sudden, so consumers tend to buy things without planned because of the atmosphere of interesting shops. Keywords: visual merchandising, store atmosphere, impulse buying